The role of neutralisation in consumers' ethical decision-making - Chatzidakis, Andreas (2008)
Consumers often behave in ways that are in apparent contradiction to their expressed ethical concerns (e.g. Carrigan and Attalla, 2001). In light of this, it is imperative that theories of consumer's ethical decision-making explain the ways in which people justify these acts to themselves and others. This thesis advances the concept of neutralisation (Sykes and Matza, 1957) in order to explore how individuals soften or eliminate the impact that counter-attitudinal and norm-contradictive behaviour can have upon their self-concept and social relationships.